Ich bilde an der Stelle \(x=u\) die Differenzfunktion.
\(d(u)=\frac{2}{3}e^{-\frac{u}{k}}\cdot (2u+3k)-2k\cdot e^{-\frac{u}{k}}\\=e^{-\frac{u}{k}} \cdot \frac{4}{3}u\)
Von dieser Funktion suche ich das Maximum:
\(d'(u)=e^{-\frac{u}{k}} \cdot(-\frac{1}{k})\cdot \frac{4}{3}u+e^{-\frac{u}{k}}\cdot \frac{4}{3} =e^{-\frac{u}{k}}(-\frac{4u}{3k}+\frac{4}{3})\)
\(e^{-\frac{u}{k}}(-\frac{4u}{3k}+\frac{4}{3})=0\) Satz vom Nullprodukt:
\(e^{-\frac{u}{k}}≠0\)
\(-\frac{4u}{3k}+\frac{4}{3}=0\)
\(u=k\)
\(d''(u)=e^{-\frac{u}{k}}\cdot (-\frac{1}{k})\cdot (-\frac{4u}{3k}+\frac{4}{3})+e^{-\frac{u}{k}}\cdot(\frac{-4}{3k})\)
\(d''(k)=e^{-\frac{k}{k}}\cdot (-\frac{1}{k})\cdot (-\frac{4k}{3k}+\frac{4}{3})+e^{-\frac{k}{k}}\cdot(\frac{-4}{3k})\)
\(d''(k)=e^{-1}\cdot (-\frac{1}{k})\cdot (0)+e^{-1}\cdot(\frac{-4}{3k})<0\) Maximum